Language Transfer Found In The Written Production Of Eleventh Grade Students On Juwiring Klaten Vocational High School 2012/2013 Academic Year - Marwanto, Marwanto; , Prof. Dr. Endang Fauziati, M. Hum; , Mauly Halwat Hikmat, Ph. D (2015)
This research is aimed at clarifying the types of language transfer, clarifying the frequencies or dominants of language transfer, and describing the sources of language transfer. In this study, the writer uses descriptive qualitative research. The research was carried out at SMKN 1 Juwiring Klaten by taking 78 students of the second grade level. The method of collecting data of this research is writing test. The results of the research showed that students make errors in language transfer. The language transfer found in the written production of the students occured on lexical level and syntactical level. The misuse of to be is the highest level in lexical transfer; it reaches 26,37% with 24 mistakes and the lowest percentage is the student transfer in using adjectives. The student transfer in agreement is the highest grade of syntactical level; it reaches 67,86% with 19 errors and the lowest is in word order. The sources of the students' language transfer committed by the students of SMKN 1 Juwiring Klaten are categorized into Selection Process, Interlanguage Identification, Blend and Autonomous Material, Structural Model, and Creating Equivalence. Some pedagogical implications concern to the teachers that have role as an agent in the education are Introducing Contrastive Analyses in Class, Applying Suitable Learning Methodology in Class, and Attractive Classroom Management.